The economic ideology of the Egyptian muslim brotherhood: the changing discourses and practices / Evrim Görmüş. - Görmüş, Evrim (Universiti Teknologi Mara Selangor, 2016)
This article aims to examine the transformation of the Muslim Brotherhood’s (MB) economic ideology since Nasser’s rule in Egypt. It argues that the MB”s economic policies were shaped by the complex nature of state-society relations in the changing political context in Egypt. As an oppositional strategy in the bi-polar political system in Egypt, the MB deviated from its liberal stance dates back to 1970s, and adopted a higly critical position against the regime’s market transformation polices by prioritizing welfare activities during the Mubarak era. The MB”s contstnat inertia in fixing its ideological inconsistencies, which was in favor of a strong state intervention in the economy, and a limited state power in politics diminished its capacity to formulate an interpretation of Islam which could be compatible with the entrepreneurial spirit and market forces during the Mubarak era in Egypt.